SOCIAL NETWORKS AS MARKETING TOOLS - ERRAGCHA, Nozha; ROMDHANE, Rabiaa (British Journal of Marketing Studies, 2014)
The aims of this paper is to reinforce the literature on the digital social networks and their influences on the marketing Having presented and categorized the digital social, networks, we highlighted , the opportunities which brings Web2.0 to the marketing. The advent of Web2.0 imposed fundamental changes which required the revalorization of the role of the consumer in the marketing approach. Indeed, this one is not passive any more, but it becomes a co-value-creating for the company.